2011
DOI: 10.3109/09638288.2010.492066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical methods for quantifying body segment posture: a literature review

Abstract: Purpose. Clinicians commonly assess posture in persons with musculoskeletal disorders and tend to do so subjectively. Evidence-based practice requires the use of valid, reliable and sensitive tools to monitor treatment effectiveness. The purpose of this article was to determine which methods were used to assess posture quantitatively in a clinical setting and to identify psychometric properties of posture indices measured from these methods or tools. Methods. We conducted a comprehensive literature review. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 80 publications
5
99
0
4
Order By: Relevance
“…This effectively means that occurrence of one body deformity creates foundations for forming new ones (1). Presented results were the most consistent findings in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This effectively means that occurrence of one body deformity creates foundations for forming new ones (1). Presented results were the most consistent findings in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…the relation between different body parts analysed within a specific timeframe and space (1). The key role in quantitative posture evaluation is placed on feet and legs, pelvis, spine, shoulders and head (2).…”
Section: Introductionmentioning
confidence: 99%
“…(20) Photogrammetry has also proved superior to VPA when the Iunes (33) study showed greater concordance between the results.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the same method as most of the other studies because Fortin et al suggested that photograph acquisition is easy, cheap, and fast. Furthermore, you can obtain objective data, such as angle or distance (28).…”
Section: Discussionmentioning
confidence: 99%